2019
DOI: 10.1002/advs.201802050
|View full text |Cite
|
Sign up to set email alerts
|

AIE Multinuclear Ir(III) Complexes for Biocompatible Organic Nanoparticles with Highly Enhanced Photodynamic Performance

Abstract: The singlet oxygen (1O2) generation ability of a photosensitizer (PS) is pivotal for photodynamic therapy (PDT). Transition metal complexes are effective PSs, owing to their high 1O2 generation ability. However, non‐negligible cellular toxicity, poor biocompatibility, and easy aggregation in water limit their biomedical applications. In this work, a series of red‐emitting aggregation‐induced emission (AIE) Ir(III) complexes containing different numbers of Ir centers (mono‐, di‐, and trinuclear) and the corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 59 publications
1
82
0
Order By: Relevance
“…The two kinds of moiety are bridged through different units such as phenyl and thiophene groups to regulate the molecular electron effect. As shown in Table 1 (AIE–PSs 9 – 19 ), most of the AIE (donor)-acceptor AIE–PSs are constructed in this way and exhibit good performance [ 42 , 56 , 58 , 59 ]. For instance, 10 and 12 , respectively, showed strong AIE with the emission enhancement up to 290-fold and 34-fold, large two-photon absorption cross-section up to 477 and 303 GM, respectively, and highly specific targeting to mitochondria in living cells with good biocompatibility [ 55 ].…”
Section: Aie-pss Based On Energy Transfer (Type Ii) Mechanismmentioning
confidence: 99%
“…The two kinds of moiety are bridged through different units such as phenyl and thiophene groups to regulate the molecular electron effect. As shown in Table 1 (AIE–PSs 9 – 19 ), most of the AIE (donor)-acceptor AIE–PSs are constructed in this way and exhibit good performance [ 42 , 56 , 58 , 59 ]. For instance, 10 and 12 , respectively, showed strong AIE with the emission enhancement up to 290-fold and 34-fold, large two-photon absorption cross-section up to 477 and 303 GM, respectively, and highly specific targeting to mitochondria in living cells with good biocompatibility [ 55 ].…”
Section: Aie-pss Based On Energy Transfer (Type Ii) Mechanismmentioning
confidence: 99%
“…To evaluate the potential biological application of probe DZ1 , imaging experiments were carried out in HepG2 cells. First, HepG2 cells hatched for 20 min in different concentrations of DZ1 solution 30. We found that DZ1 passed through the cell membrane and stained mitochondria with an optimum concentration of 10 μM (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…[46][47][48][49][50][51][52][53][54] Recently, our group obtained three red-emitting AIEgen nanoparticles (NPs) with higher brightness, enhanced 1 O 2 generation, and better biocompatibility compared to the pure iridium(III) complexes. 55 These precedents make AIE NPs with purely organic D-A units particularly suitable as smart PSs to successfully obtain an "all-in-one" (image-guided PDT, ultrafast staining and long-term tracing) system.…”
Section: Introductionmentioning
confidence: 99%